Influence of CT metal artifact reduction on SPECT/CT quantification of bone scintigraphy – Retrospective study for selected types of metal implants - Kugler, Amelie; Kuwert, Torsten; Ritt, Philipp; Grings, Andreas (Nuklearmedizin - NuclearMedicine, 2022)
Aim Implanted metal prostheses can cause severe artifacts in reconstructed computed tomography (CT) images. To reduce the diagnostic impact of these artifacts and improve attenuation correction in single photon emission computed tomography (SPECT), an algorithm of iterative metal artifact reduction (iMAR) for SPECT/CT systems was developed. The aims of this study were (a) to assess the difference in visual image quality by comparing CT and SPECT images reconstructed with and without iMAR and (b) to determine the influence of iMAR on quantitative 99mTc-uptake in SPECT/CT.Methods This retrospective study includes 21 patients with implanted metal prostheses who underwent SPECT/CT bone scintigraphy. CT data were reconstructed with iMAR and without (noMAR) and were used for attenuation correction of SPECT data for xSPECT Quant and xSPECT Bone reconstruction. The effect of iMAR on image quality was evaluated by visual analysis and the effect on quantitative SPECT/CT was assessed by measuring HU values and absolute uptake values (kBq/mL) in volumes of interest (VOIs).Results There was a significant reduction of visible metal artifacts with iMAR (p<0.01) in the CT images, but visual differences in the SPECT images were minor. The values of quantitative tracer uptake in VOIs near metal implants were lower for iMAR vs. noMAR xSPECT Quant (p<0.01). Only VOIs near metal showed significant differences in HU values, which were 14.6% lower for iMAR CT (p<0.01).Conclusion The use of iMAR reduces metal artifacts in CT and improves the perceived image quality. Although in some cases a significant difference in the quantitative evaluation of SPECT/CT was observed, the influence of iMAR can be considered small in relation to other factors in the clinical setting.
Keywords: iMAR; Bone-Scintigraphy; quantitative SPECT reconstruction; metal artifacts; Tc-99m-DPD